Identifying the link between chemical exposures and breast cancer in African American women via integrated in vitro and exposure biomarker data. (November 2021) - Polemi, Katelyn M.; Nguyen, Vy K.; Heidt, Julien; Kahana, Adam; Jolliet, Olivier; Colacino, Justin A.
Highlights: There are breast cancer racial disparities, and the drivers are poorly understood. Black women are highly exposed to chemicals with untested links to breast cancer. We linked biomonitoring and toxicity screening data to predict chemical effects. Black women are exposed to chemicals with breast cancer activity at relevant doses. Abstract: Among women, breast cancer is the most prevalent form of cancer worldwide and has the second highest mortality rate of any cancer in the United States. The breast cancer related death rate is 40 % higher in non-Hispanic Black women compared to non-Hispanic White women. The incidence of triple negative breast cancer (TNBC), an aggressive subtype of breast cancer for which there is no targeted therapy, is also approximately three times higher for Black, relative to, White women. The drivers of these differences are poorly understood. Here, we aimed to identify chemical exposures which play a role in breast cancer disparities. Using chemical biomonitoring data from the National Health and Nutrition Examination Survey (NHANES) and biological activity data from the EPA's ToxCast program, we assessed the toxicological profiles of chemicals to which US Black women are disproportionately exposed. We conducted a literature search to identify breast cancer targets in ToxCast to analyze the response of chemicals with exposure disparities in these assays. Forty-three chemical biomarkers are significantly higher in Black women. Investigation of these chemicals in ToxCast resulted in 32, 683 assays for analysis, 5172 of which contained nonzero values for the concentration at which the dose-response fitted model reaches the cutoff considered "active". Of these chemicals BPA, PFOS, and thiram are most comprehensively assayed. 2, 5-dichlorophenol, 1, 4-dichlorobenzene, and methyl and propyl parabens had higher biomarker concentrations in Black women and moderate testing and activity in ToxCast. The distribution of active concentrations for these chemicals in ToxCast assays are comparable to biomarker concentrations in Black women NHANES participants. Through this integrated analysis, we identify that multiple chemicals, including thiram, propylparaben, and p, p' DDE, have disproportionate exposures in Black women and have breast cancer associated biological activity at human exposure relevant doses.